2016
DOI: 10.1016/j.compstruct.2016.09.045
|View full text |Cite
|
Sign up to set email alerts
|

On the statistics of transverse permeability of randomly distributed fibers

Abstract: An RVE-based stochastic numerical model is used to calculate the permeability of randomly generated porous media at different values of the fiber volume fraction for the case of transverse flow in a unidirectional ply. Analysis of the numerical results shows that the permeability is not normally distributed. With the aim of proposing a new understanding on this particular topic, permeability data are fitted using both a mixture model and a unimodal distribution. Our findings suggest that permeability can be fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In numerical model analysis, the RVE size needs to be large enough to describe the inherent properties of the material, however, when considering the computational cost, the size of the RVE was expected to be relatively small. Bodaghi et al [ 43 ] found that the expected value and SD of the statistical analysis of the numerical results tend to converge when the delta is greater than or equal to 30. Trias [ 44 ] suggests that the minimum value of ζ is 50, and ζ = 50 was used in this paper.…”
Section: Statistical Analysis Of Spatial Point Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…In numerical model analysis, the RVE size needs to be large enough to describe the inherent properties of the material, however, when considering the computational cost, the size of the RVE was expected to be relatively small. Bodaghi et al [ 43 ] found that the expected value and SD of the statistical analysis of the numerical results tend to converge when the delta is greater than or equal to 30. Trias [ 44 ] suggests that the minimum value of ζ is 50, and ζ = 50 was used in this paper.…”
Section: Statistical Analysis Of Spatial Point Patternsmentioning
confidence: 99%
“…Periodic boundary conditions was applied to the edge of the RVE region, as shown in Figure 9, while the fiber surface was defined as the wall boundary condition, Δ p is arbitrary nonzero pressure difference, and the permeability is independent of the applied pressure difference. [ 43 ] The following is Equation ): {pinpout=normalΔpp1p2=0 …”
Section: Numerical Modelmentioning
confidence: 99%
“…In general, it is difficult to obtain uniform matrix distribution during fabricating UDL because of close-packing of fibers, which results in the existence of fiber-clusters and resin-rich zones. [20] With decrease of ply thickness, the close-packing layers of fibers decrease, which allows more penetration of matrix into gaps between fibers. This slightly increases the average spacing in fiber-cluster zone while decreases the thickness of resin-rich zones.…”
Section: Fiber Contact Ratio In the Fibercluster Zonementioning
confidence: 99%
“…where χ is a shape factor to describe the difference of the fiber distribution between the transverse and the thickness directions. [20] R r = R f s i ψW ð11Þ…”
Section: Resistivity In the Thickness Directionmentioning
confidence: 99%
See 1 more Smart Citation